DRY MATTER PRODUCTION AND NUTRIENT UPTAKE OF RICE (Oryza sativa L.) AS INFLUENCED BY SYSTEMS OF CULTIVATION AND IRRIGATION REGIMES IN PUDDLED SOIL - M. UMA DEVI, A. SATHISH, P. RAGHURAMI REDDY, K. AVIL KUMAR and (The Journal of Research, PJTSAU, 2017)
Manual transplanting is the most common practice of rice cultivation in South and South East Asia. In India, 44 per cent area (19.6 M ha) is undertransplanting in irrigated lowlands. It is not only time consuming, but also laborious requiring about 30 man days ha-1 besides causing drudgery to women folk. This technique also results in non-uniform and inadequate crop stand (Rajendra Prasad, 2004). In all rice growing countries, there is an acute shortage of human labour during transplanting period due todiversion of labour to non agricultural sectors resulting in delay of transplanting, reduced yield and lesser profit. In the context of acute labour shortage, the traditional method of transplanting becomes ratherdifficult to ensure timely planting with optimum age of seedling. To overcome these difficulties transplanting can be substituted by direct seeding and machine transplanting which could reduce labour needs by more than 20 per cent and increase the yields.